Enteral nutrition ameliorates the symptoms of Crohn's disease in mice via activating special pro-resolving mediators through innate lymphoid cells - Di Zhao (SAGE Publishing, 2021)
Crohn's disease activates the inflammatory reactions to induce intestinal disorders. Enteral nutrition (EN) could exert general immunomodulatory effects. Cecal ligation and perforation (CLP) surgery was utilized to establish Crohn's disease mice models. Survival analysis, hematoxylin-eosin staining, flow cytometry, ELISA, Western blot and liquid chromatography-tandem MS were applied. Baicalein was added to inhibit lipoxygenases. The survival rate was restored and inflammatory injury, exudate neutrophils in peritoneal lavage and serum levels of IL-6 and TNF-α were ameliorated by EN treatment as compared with CLP treatment. EN also increased ILC-3 content, 5/15-LOX level and RvD1-RvD5 in peritoneal lavage. Baicalein reversed all the detected effects of EN except ILC-3 content. EN could activate special pro-resolving mediators (SPMs) through ILCs to mitigate injuries of Crohn's disease.